(untitled) (The International Journal of Educational Sciences and Arts, 2024)
The research aims to find out the effectiveness of Chatbots in developing scientific research skills and motivation for learning among postgraduate students. The experimental approach with one group quasi-experimental design was used, on a sample consisting of (27) female students. The research tools were testing students’ skills of scientific research methodology, scientific referencing, as well as measuring students’ motivation to learn. The results revealed that there is a statistically significant difference between the mean scores of the female students at the significance level (α≤0.05) in the application of the pre and post-test. This result gives an indication of the effectiveness of Chatbots in developing scientific research skills in terms of scientific research methodology and scientific referencing for postgraduate students. In addition to the presence of a statistically significant difference in the measure of motivation to learn, which confirms the effectiveness of Chatbots in developing motivation to learn and the students’ satisfaction with the use of chat bots in learning scientific research skills. Therefore, the research recommends expanding the use of Chatbots in teaching various educational courses. It is suggested that more research could be conducted on the impact and effectiveness of interactive Chatbots in the educational process.